SEJARAH PEMAHAMAN 350 TAHUN INDONESIA DIJAJAH BELANDA - Absiroh, Ulil; ', Isjoni; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Judged nation of Indonesia colonized by Dutch for 350 years need investigations back to prove its truth. It is not only through the political approach, but also need the law approach. Through the law approach, Resink had showed the force proofs that the nation of Indonesia (firstly called by Nusantara) not all of its colonized by Dutch-Indies Government. As for being the writer purpose in this research are to be aware the arrival of Dutch to Nusantara, to be aware of Dutch political system to occupied in Nusantara, to be aware the background of understanding about 350 years Indonesia colonized by Dutch. Method that is used in this research was history and documentary. Data are obtainable through literature technique and documentation. The result from this research had showed that is not 350 years Indonesia colonized by Dutch, with proofs that are: mentioning of Indonesia's name, law of nations at Makassar in the past, kings and kingdoms that independent in Nusantara at 1850-1910's. Resink calculation, In fact, Dutch only occupied all of Nusantara for 40 until 50 years. However, the writer makes a conclusion that the reality Indonesia colonized by Dutch only for 30 years since the conquest of Aceh in 1912. So since 1912 all regions of Indonesia official colonized by Dutch until in 1942. The understanding 350 years Indonesia colonized by Dutch created by politicians of Indonesia honestly had been to positive values, the purpose to dig up nationalism and patriotism nation of Indonesia, and legitimacy association and federation from nation of Indonesia because condition of nation of Indonesia was separated, and to replaced fight spirits nation of Indonesia. However, the understanding about 350 years Indonesia colonized by Dutch had impacted for composing Indonesia history because it is not historically fact.Key Words: 350 Years, Indonesia, Colonized, Dutch.